Acute kidney injury (AKI) post-mRNA SARS-CoV-2 vaccine in patients with cancer, treated with immune check point inhibitor (ICPi): An immune double whammy!. Issue 1 (February 2023) - Baker, Richard; Gosalia, Kinjal; Jhaveri, Kenar D; Gudsoorkar, Prakash
Background: Immune check point inhibitors (ICPi) have become the first line treatment for most of the cancers and have shown promising results. However, they can provoke reactions, the most feared being immune related adverse events (irAE). Case presentation: We present a series of three cases, of patients recieving ICPi. All three patients developed AKI after administration of SARS-CoV-2 mRNA vaccine. Two patients had kidney-biopsy-proven acute interstitial nephritis (AIN) which responded to ICPi discontinuation and treatment with steroids. One had presumed AIN based on the high levels of CRP and urine retinol binding protein to creatinine ratio and responded to cessation of ICPi alone. Conclusion: These three cases demonstrate that a strong immune response from the SARS-CoV-2 mRNA vaccine combined with an uninhibited immune system under influence of ICPi led to an amplification of autoimmunity leading to AKI presenting as AIN.